ANALYSIS OF MANAGERIAL COMPONENTS IN MOSQUITO VECTORS (AEDES AEGYPTI) CONTROL IN THE BUFFER AREA OF THE CLASS 1 SURABAYA PORT HEALTH OFFICE - Fauzia Yulianti Ramadhani (Universitas Airlangga, 2021)
ABSTRACTThe Aedes aegypti index in the buffer area of the Class 1 Surabaya Port Health Office was in accordance with the Standard Operating Procedures (SOP) as stated in the Regulation of the Indonesian Ministry of Health Number 431 of 2007 (431/MENKES/SK/IV/2007) on Technical Guidelines for Control of Environmental Health Risks in Ports/Airports/Cross-Border in the Context of Health Quarantine. The Port Health Office has responsibilities to control environmental risks, one of which was the Aedes aegypti mosquitos in the borders. This study was descriptive observational and aimed to analyze the managerial components in Aedes aegypti mosquito control in the buffer area ofthe Class 1 Surabaya Port Health Office in Surabaya. The research variables (factors that determine control activities) were manpower, money, methods, materials, markets, machines, and information. The research subjects were two officers at Class 1 Surabaya Port Health Office and five cadres who monitored larva. Data were analyzed descriptively. The results explained that manpower, money, materials, market, technology, and information were all in accordance with the SOP of the Surabaya Port Health Office. However, the larva survey method did not comply with the SOP as officers still used the visual method. It was concluded that managerial components in Aedes aegypti control by Class 1 Surabaya Port Health Office followed the SOP except in their larva survey method. The researchers recommended carrying out a larva survey method by taking 1 larva from each container (single larva) at a time. Keywords: Aedes aegypti, control vector, managerial components.